Webster's New Twentieth Century Dictionary of The English Language, Unabridged - Noah Webster 1758-1843; Jean Lyttleton Mckechnie 1925- (UK Collins, 1975)
based upon the broad foundations laid down by Noah Webster
Keywords: Languages (3GddZGJs; General -- Dictionaries; English language; Deluxe Color